2018
DOI: 10.1055/s-0038-1668150
|View full text |Cite
|
Sign up to set email alerts
|

State of Play: Eight Decades of Surgery for Esophageal Atresia

Abstract: Including a full range of articles reflecting the heterogeneity of EA, mortality rate significantly decreased during the course of 80 years. Along with the decrease in mortality, there is a shift to the importance of major postoperative complications and long-term morbidity regardless of surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 120 publications
1
33
0
7
Order By: Relevance
“…1,2 The malformation is characterized by a discontinuity of the esophagus with or without tracheoesophageal fistula. Since the first successful primary repair of esophageal atresia in 1941, improvements in operative and perioperative care have led to better outcomes, and mortality has decreased to a single-digit range [3][4][5] with most deaths due to comorbidities. Evolution from concerns about mortality to concerns about morbidity and quality-of-life issues has occurred, 5 and long-term morbidity remains high until adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The malformation is characterized by a discontinuity of the esophagus with or without tracheoesophageal fistula. Since the first successful primary repair of esophageal atresia in 1941, improvements in operative and perioperative care have led to better outcomes, and mortality has decreased to a single-digit range [3][4][5] with most deaths due to comorbidities. Evolution from concerns about mortality to concerns about morbidity and quality-of-life issues has occurred, 5 and long-term morbidity remains high until adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal stricture, anastomotic leakage, and recurrent TEF are well‐known complications after EA repair. Previous studies found the esophageal stricture rate to vary between 25% and 42%, the anastomotic leakage rate between 11% and 23%, and the recurrent TEF rate between 4% and 9% . In a recent meta‐analysis, a comparison of thoracoscopic and open approaches found that the thoracoscopic approach notably reduced the length of hospital stay and time to oral refeeding, but it was associated with a longer operative time.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found the esophageal stricture rate to vary between 25% and 42%, the anastomotic leakage rate between 11% and 23%, and the recurrent TEF rate between 4% and 9%. 2,3 In a recent meta-analysis, a comparison of thoracoscopic and open approaches found that the thoracoscopic approach notably reduced the length of hospital stay and time to oral refeeding, but it was associated with a longer operative time. The rate of postoperative complications, such as leaks and strictures, was similar between both approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations